Hubungan Kepercayaan Diri Dengan Komunikasi Interpersonal Siswa SMP - Linda Lestari; Muswardi Rosra; Shinta Mayasari (ALIBKIN (Jurnal Bimbingan Konseling), 2019)
The problem in this research is the low of students interpesonal communication. The purpose of this study to determine the correlation of self confidence with interpersonal communication in class VIII students at SMP Negeri 9 Bandar Lampung. This research is quantitative descriptive. The population in this study amounted to 288 students with a sample of 158 students obtained through simple random sampling techniquest. The data collection techniques using a scale interpersonal communication and scale self confidence. The data analysis techniques using Product Moment Correlation. The research results obtained value r count = 0,414 r table = 0,159 then Ho is rejected and Ha is accepted, which means there is a positive and significant correlation of self confidence with interpersonal communication. If the students self confidence is high then students interpersonal communication will also be high.Masalah dalam penelitian ini adalah komunikasi interpersonal siswa rendah. Tujuan penelitian ini adalah untuk mengetahui hubungan kepercayaan diri dengan komunikasi interpersonal siswa kelas VIII SMP Negeri 9 Bandar Lampung. Peneitian ini merupakan penelitian deskriptif kuantitatif. Populasi penelitian berjumlah 288 siswa dengan sampel 158 siswa yang diperoleh melalui teknik simple random sampling. Teknik pengumpulan data menggunakan skala komunikasi interpersonal dan skala kepercayaan diri. Teknik analisis data menggunakan korelasi Product Moment. Hasil penelitian diperoleh r hitung = 0,414 r tabel = 0,159, Ho ditolak dan Ha diterma, yang artinya terdapat hubungan yang positif dan signifikan antara kepercayaan diri dengan komunikasi interpersonal. Jika kepercayaan diri siswa tinggi maka akan diikuti komunikasi interpersonal siswa yang tinggi pula.Kata kunci: hubungan, kepercayaan diri, komunikasi interpersonal